Quiver Sebagai Media Pengajaran Alfabet pada Sekolah Dasar: Studi Deskriptif: Penelitian - Abdul Aziz; Herry Wahyudi Susanto; Widyawati; Yuliana Nurhayati; M. Agus Safrian Nur; Febri Irwandi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the use of Quiver, an augmented reality (AR)-based media, in teaching the alphabet at the elementary school level. Technological innovation in education has opened various opportunities, including the use of interactive media such as Quiver, which enables the three-dimensional visualization of letters. This study employed a qualitative descriptive approach, with early grade elementary school students as research subjects. Data were collected through observation, interviews, and documentation of learning activities involving the use of Quiver. The results indicate that the use of Quiver enhances students’ learning enthusiasm, facilitates the recognition of letter shapes and sounds, and creates a more interactive and engaging learning atmosphere. Moreover, teachers reported that the media supports the delivery of material effectively by integrating visual, auditory, and kinesthetic elements. This study recommends Quiver as an effective alternative media for teaching the alphabet, particularly at the elementary level. In the future, the development of similar media can be directed toward basic literacy and numeracy content.